Performance evaluation of currently available VLSI implementations satisfying U-interface requirements for an ISDN in South Africa. - Kaplan, Paul Charl (My University, 1990)
This project report examines the performance of three VLSI U-interface implementations satisfying the requirements of Basic Access on an ISDN. The systems evaluated are the Intel 89120,Siemens PEB2090 and STC DSP144, operating on 2BIQ, MMS4J and SU32 line codes respectively. Before evaluating the three abovementioned systems, a review of the underlying principles of U-interface technology is presented. Included in the review are aspects of transmission line theory, line coding, echo-cancellation, decision feedback equalisation, and pulse density modulation. The functional specifications of the three systems are then presented followed by a practical evaluation of each system. As an aid to testing the transmission systems, an evaluation board has been designed and built. The latter provides the necessary functionality to correctly activate each system, as well as the appropriate interfacing requirements for the error-rate tester. The U-interface transmission systems are evaluated on a number of test-loops, comprising sections of cable varying in length and gauge. Additionally, impairments are injected into data-carrying cables, in order to test the performance of each system in the presence of noise. The results of each test are recorded and analysed. Finally, a recommendation is made in favour of the 2BIQ U-interface. It is shown to offer superior transmission performance, at the expense of a slightly higher transmit-power level.
A project report submitted to the Faculty of Engineering, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Science in Engineering.
Keywords: Integrated services digital networks.